PERBANDINGAN KRITERIA 29 DENGAN IMKAN AL-RUKYAT MABIMS DALAM PENENTUAN AWAL BULAN HIJRIAH - Sari, Ulfa Awaliya; Aisyah , Nur (Universitas Islam Negeri Alauddin Makassar, 2025)
Abstrack This thesis discusses the comparison of criterion 29 with Imkan-Al Rukyat MABIMS in determining the beginning of the month. The formulation of the problem in the thesis is 1) How the concept of criterion 29 with Imkan al-rukyat MABIMS, 2) How does criterion 29 compare with Imkan al-rukyat MABIMS. This research uses library research in the sense of looking for articles, theses, journals, books that have a relationship with the title in the author. The approach used by the author is to use a shari'i approach and an astronomical approach. According to the data source, the data in this study is divided into two data, namely primary data and secondary data. The results of criterion 29 and the imkan al-rukyat MABIMS method have several similarities and differences. The similarities are orientation to hilal observation, hilal visibility criteria, observation methods, and linkage with the Hijri calendar. Both have a similar orientation to hilal observation by looking for early signs of the Hijri month through direct observation of the hilal, by establishing hilal visibility observation criteria that include factors such as the age of the moon, lunar elevation, lunar elongation angle, atmospheric conditions, and geographical position. This study is expected to help improve understanding of the comparison of criterion 29 and the method of imkan al-rukyat MABIMS in determining the beginning of the Hijri month. Similarly, it can add insight into the similarities and differences between the two criteria.